Estrogenic Regulation of the GnRH Neuron - Radovick, Sally (Frontiers in Endocrinology, 2012)
Reproductive function is regulated by the secretion of luteinizing hormone (LH) and follicle-stimulating hormone from the pituitary and the steroid hormones from the gonads. The dynamic changes in the levels of the reproductive hormones regulate secondary sex characteristics, gametogenesis, cellular function, and behavior. Hypothalamic GnRH neurons, with cell bodies located in the basal hypothalamus, represent the final common pathway for neuronally derived signals to the pituitary. As such, they serve as integrators of a dizzying array of signals including sensory inputs mediating information about circadian, seasonal, behavioral, pheromonal, and emotional cues. Additionally, information about peripheral physiological function may also be included in the integrative signal to the GnRH neuron. These signals may communicate information about metabolic status, disease, or infection. Gonadal steroid hormones arguably exert the most important effects on GnRH neuronal function. In both males and females, the gonadal steroid hormones exert negative feedback regulation on axis activity at both the level of the pituitary and the hypothalamus. These negative feedback loops regulate homeostasis of steroid hormone levels. In females, a cyclic reversal of estrogen feedback produces a positive feedback loop at both the hypothalamic and pituitary levels. Central positive feedback results in a dramatic increase in GnRH secretion (Moenter et al., 1992; Xia et al., 1992; Clarke, 1993; Sisk et al., 2001). This is coupled with an increase in pituitary sensitivity to GnRH (Savoy-Moore et al., 1980; Turzillo et al., 1995), which produces the massive surge in secretion of LH that triggers ovulation. While feedback regulation of the axis in males is in part mediated by estrogen receptors (ER), there is not a clear consensus as to the relative role of ER versus AR signaling in males (Lindzey et al., 1998; Wersinger et al., 1999). Therefore, this review will focus on estrogenic signaling in the female.